Search for the optimal temperature regime for the synthesis of benzylidenebenzylamine based on genetic algorithms - Antipina, E V; Mustafina, S A; Antipin, A F; Podval'nyi, E S (Journal of physics. Conference series, 2020)
The article is devoted to the creation of an algorithm for finding the optimal temperature regime of a chemical reaction based on evolutionary calculations. The problem of optimal control for a chemical process is formulated in a general way. A genetic algorithm for solving the problem is described. A computational experiment was carried out for the synthesis reaction of benzylidenebenzylamine in order to obtain the maximum yield of the product during the reaction. The optimum temperature profile and the optimal concentration of reagents were obtained. Based on the formulated genetic algorithm, a program was developed in the visual programming environment Delphi, which allows finding the optimal temperature profile of the chemical process.